Rattus hoogerwerfi Chasen 1939 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus hoogerwerfi Chasen 1939 Rattus hoogerwerfi Chasen 1939, Treubia, 17 (3): 496. Type Locality: Indonesia, W Sumatra, Aceh, Gunung Leuser, Blang Kedjeren, 2900 ft (885 m). Vernacular Names: Hoogerwerf's Sumatran Rat. Distribution: Recorded from only between 885 and 2835 m in foothills and upper slopes of Gunung Leuser, Sumatra (Musser, 1986). Conservation: IUCN – Vulnerable. Discussion: Rattus species group unresolved. Very distinctive and possibly not a member of Rattus . Morphology and comparisons with other species documented by Musser and Newcomb (1983) and Musser (1986). Although phylogenetic affinities with species of Rattus from Sulawesi, the Philippines, and Christmas Isl have been claimed (Miller, 1942), and with R. korinchi (Chasen, 1939), no compelling evidence links R. hoogerwerfi with any other species (Musser, 1986). Member of the suite of murine species endemic to Sumatra (see Musser, 1986, and account of Maxomys hylomyoides ). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Muridae, pp. 1189-1531 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 1472, DOI: 10.5281/zenodo.7316535